# How do you solve # 2/3 = 2 - (5x-3)/(x-1)#?

Arrange the equation and get

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 2/3 = 2 - (5x-3)/(x-1), we can start by multiplying both sides of the equation by the common denominator, which is (x-1). This will help us eliminate the fractions.

First, multiply 2/3 by (x-1):

(2/3)(x-1) = 2(x-1) - (5x-3)

Next, simplify both sides of the equation:

2(x-1) = 2(x-1) - (5x-3)

Expand the equation:

2x - 2 = 2x - 2 - 5x + 3

Combine like terms:

2x - 2 = -3x + 1

Move all the variables to one side of the equation:

2x + 3x = 1 + 2

Combine like terms:

5x = 3

Divide both sides of the equation by 5:

x = 3/5

Therefore, the solution to the equation 2/3 = 2 - (5x-3)/(x-1) is x = 3/5.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- How do you simplify #(9y + 8) / (y)# and what are the restrictions?
- How do you find points of discontinuity in rational functions?
- How do you solve #(2x)/(4-x)=x^2/(x-4)#?
- How do you solve rational equations #81.9=((0.1+2x)^2)/((0.1-x)(0.1-x))#?
- If y varies inversely as x. When x = 6, y = 2. How do you find x when y = 12?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7